Estrutura, personagens e enganos: introdução - Cláudia Teixeira (Autores Gregos e Latinos - Ensaios, 2016)
This publication presents an introductory study, of didactic nature, to Plautus' Bacchides. Aspects related to the context, the characteristics, the structure and the characters of the play are discussed, as well as the problem of Plautus' originality regarding the creation of the 'third deception'.